ANALISIS FAKTOR YANG MEMPENGARUHI LOYALITAS PERUSAHAAN PELANGGAN (Studi pada Pelanggan PT WAN HAI Ltd di Jawa Tengah) - Mulyanto, Kukuh (STIE Totalwin Semarang, 2010)
This studyÂ intent to search several variablesâ effect which is probably able to rise loyalty and firm performance. The study used several customer of WAN HAI Ltd in Midle of Java as sample. Data analyze instrument used by the writer is AMOS 4. Data analyze result shows that the research model has well appropriateness and all hypothesis of the study are able to be evidenced. Summary said that satisfaction, reputation, price, are positively effected to loyalty, andÂ loyalty are positively effected to firms performance. Result of research proves that satisfaction, reputation, and price has positive influence and significant to loyalty. Loyalty has positive influence and signifaicant to firm performance. Managerial implication given to the company is suggestion or input to management to concern the price factors, as it is the most dominant factor effected to loyalty. The researchâs limitation is that it is case study so that the result is not able to be generalized